Spontaneous Adverse Drug Reaction Reporting by Health Consumers in Canada: A Multi-Methods Study - Al dweik, Rania (Université d'Ottawa / University of Ottawa, 2016)
Monitoring adverse drug reactions (ADRs) through pharmacovigilance is vital to health consumer safety. Health Canada accepts ADR reports from physicians, health consumers, lawyers and manufacturer. This study uses a multi-methods approach to evaluate health consumers ADR reporting to pharmacovigilance programs. Methods: Guided by Risk Perception Theory, this study involved three phases. 1) A systematic review to identify factors influencing health consumer ADR reporting 2) An observational study to compare health consumer and physician ADR reports received by Health Canada from 2000-2014 to determine differences in seriousness, system organ class, and anatomical therapeutic class. 3) A qualitative study to explore health consumers’ experiences with ADR reporting and usability of the Canadian Vigilance ADR system. Results: 1) Of 1435 citations identified, 22 studies were eligible. Common barriers for health consumers to report ADRs were poor awareness and confusion on who should report. Common motives were preventing ADRs in others and wanting feedback. 2) Of 198,781 ADR reports, 57,078 (29.0 %) were from health consumers and 52,843 (27.0%) from physicians. Compared to physicians, health consumers reported significantly more ADRs (serious and non-serious) (p<0.0001) and reported differently for organ systems affected and by types of medication. 3) Interviews from 15 adult health consumers revealed barriers (e.g., poor awareness about the available reporting systems) and motives for reporting ADRs (e.g., intolerable side effect impacting daily activities). Few were aware of the Canadian Vigilance reporting system and usability was limited by the number and complexity of questions. Conclusion: Health consumer role in directly reporting ADRs is influenced by several factors. In Canada, most were unaware of the Canadian Vigilance System and unclear about their role in reporting ADRs. Quarters of Canadian ADRs are reported by health consumers and their ADRs had different characteristics from physicians. These findings are relevant to policymakers, public health officials, and regulatory agencies for improving medication safety in Canada and worldwide.
Keywords: Adverse drug reaction; Canada; Health Consumers; Perception